Testing the least-squares Monte Carlo method for the evaluation of capital requirements in life insurance - Massimo Costabile; Fabio Viviano (Risks, 2020)
In this paper, we test the efficiency of least-squares Monte Carlo method to estimate capital requirements in life insurance. We choose a simplified Gaussian evaluation framework where closed-form formulas are available and allow us to obtain solid benchmarks. Extensive numerical experiments were conducted by considering different combinations of simulation runs and basis functions, and the corresponding results are illustrated.
Keywords: G22; 330; least squares Monte Carlo; Solvency capital requirements; value at risk; Lebensversicherung; Kapitalbedarf; Risikomaß; Monte-Carlo-Simulation; Kleinste-Quadrate-Methode